Coherent light-matter interactions in quantum confined halide perovskites - Cai, Rui (Nanyang Technological University, 2025)
Coherent light-matter interactions provide exciting opportunities for tuning the interplay among excitations, which are of significant interest and of central importance for advancing fundamental physics and the development of optical quantum technologies. In semiconductors, such interactions have been intensively investigated by using ultrafast pump-probe techniques with impressive time resolution. However, in conventional semiconductors the coherence and/or matter state (e.g., excitonic state) are severely undermined by temperature. In recent years, lead halide perovskites (LHPs) emerge as a promising platform for quantum and ultrafast photonics, owing to their outstanding optoelectronic and optospintronic properties at rather high temperatures. Particularly, the presence of room temperature stable excitons offers a new approach for manipulating light and their interactions in these materials. This dissertation presents a comprehensive understanding of several coherent phenomena in quantum confined structures of LHPs and establishes methods to manipulate the coherence from both optical and material perspectives. Specifically, a biexciton-mediated optical Stark effect is demonstrated in layered perovskites by transient absorption spectroscopy, with which the exciton resonance can be deterministically engineered energetically depending on driving energy and excitation intensity. Using quantum beating spectroscopy, the excitonic quantum coherence is established in CsPbBr3 nanocrystals, where the coherence between two exciton fine structure splitting states can further be manipulated by the polarization of interacting photons. In addition, the spin decoherence mechanisms of optically orientated excitons are unambiguously uncovered. Lastly, the bulk polariton properties which reflect the intrinsic strong exciton-photon coupling of 2D perovskite crystals are revealed by time-of-flight measurements. These findings provide fresh insights into coherent light-matter interactions in low-dimensional LHPs, highlighting their potential as promising candidates for quantum photonic technologies.